Faham Emanasi Dalam Filsafat - Muhmmad Rusdi Rasyid (LPPM IAIN Sorong, 2016)
Emanation becomes the first mover classical philosophy. There are always faced with two contradictory as that work and that done, spirit and matter, the creator and the created. The first mover places outside natural birth, transcendental nature. This understanding implies the ultimate reality which is the source of all things, which is God, which then appear in another reality in the source with the overflow. The human world is an emanation of the soul while the soul is an emanation of the Spirit (Nous), and the spirit of the first emanation from the one (To Hen). World unite, as possessed by the Soul of the World as the emanation of Soul. The world and man is distinguished, but basically everything is permeated by the power and light source, namely the One. The appearance of the home then this is the nature of the origin as the emergence of heat from the embers emergence of light from the light source. Which was the cause and origin of the foundation of everything, and which then emerges from the origin of it by itself without moving, without want, without approval. This article elaborates the world of emanation in general.